Iatrogenic Severe Splenic Injury after Colonoscopy - Ikponmwosa Enofe; Jacob Burch; Julie Yam; Manoj Rai (Case Reports in Gastrointestinal Medicine)
Colonoscopy is a low-risk procedure performed for screening and diagnostic purposes. About 15 million colonoscopies were carried out in the United States in 2012 with this number projected to increase. Injury to the spleen as a complication of colonoscopy is still a rather rare occurrence. We report a case of significant splenic injury, American Association of Surgery for Trauma (AAST) grade III with hemoperitoneum, in a patient following diagnostic colonoscopy, managed conservatively without the need for invasive or salvage surgical procedure.